Antihypertensive effect of Cecropia obtusifolia (Moraceae) leaf extract on rats - Salas, Isaías (Universidad de Costa Rica, 1987)
A lyophilized aqueous leaf extract of Cecropia obtusifolia proved to be antihypertensive when intravenously administrated to conscious spontaneous hypertensive rats. Forty-five minutes after injection, the maximum fall in arterial pressure (-23.5% relative to preinjection values) was seen and recovery was not complete by the end of the 1 80 min observation periodo The extract was also given to pre-hypertensive SHR and normotensive rats. The fall in blood pressure was more conspicuous in the two SHR groups and was not accompanied by changes in cardiac frequency in any group. This would appear to rule out either a direct or indirect involvement of the heart in regard to the observed hypotension.